Creutzfeldt-Jackob disease: A Case Report with MRI (DWI) Findings - Joshi, Hari Om; Dan, Tong; Yuan, Ting Tang; Thapa, Ajit; Shakya, Jyotsna (Nepal Journal of Medical Sciences, 2019)
Transmissible Spongiform Encephalopathy is sub-acute transmissible neurodegenerative disease which affects both human and animals. Among those that affect humans, Creutzfeldt- Jakob disease is the most common. This disease has a genetic basis and characteristic of an infectious disease. Magnetic Resonance Imaging is an important tool in diagnosis of Creutzfeldt-Jakob disease and can assist especially in the early stages of the disease, when the clinical features might not be typical and Electroencephalogram shows normal or nonspecific abnormalities. Newer Magnetic Resonance Imaging techniques such as Diffusion Weighted Imaging have shown to be more sensitive in detecting this disease at its early stage. We report a single case of probable Creutzfeldt-Jakob disease and its peculiar findings on brain magnetic resonance imaging.